196k views
2 votes

\displaystyle \rm \sum_(n = 0)^ \infty \frac{(n! {)}^(2) }{(2n + 1)!}

User Groozin
by
4.4k points

1 Answer

5 votes

Observe that


((n!)^2)/((2n+1)!) = (n!(2n-n)!)/((2n+1)(2n)!) = \frac1{(2n+1)\binom{2n}n}

Starting with a well-known series


\displaystyle 2\arcsin^2(x) = \sum_(n=1)^\infty \frac{(2x)^(2n)}{n^2 \binom{2n}n}

we take some (anti)derivatives to find a sum that more closely resembles ours.

Let
f(x)=2\arcsin^2(x). Then


\displaystyle f'(x) = 2 \sum_(n=1)^\infty \frac{2^(2n) x^(2n-1)}{n \binom{2n}n}


\displaystyle x f'(x) = 2 \sum_(n=1)^\infty \frac{2^(2n) x^(2n)}{n \binom{2n}n}


\displaystyle x f''(x) + f'(x) = 4 \sum_(n=1)^\infty \frac{2^(2n) x^(2n-1)}{\binom{2n}n}


\displaystyle x^2 f''(x) + x f'(x) = 4 \sum_(n=1)^\infty \frac{2^(2n) x^(2n)}{\binom{2n}n}

Noting that both sides go to zero as
x\to0, by the fundamental theorem of calculus we have


\displaystyle \sum_(n=1)^\infty \frac{2^(2n) x^(2n+1)}{(2n+1)\binom{2n}n} = \frac14 \int_0^x (t^2 f''(t) + t{}f'(t)) \, dt

so that when
x=\frac12, and rearranging some factors and introducing a constant, we recover a useful sum.


\displaystyle \sum_(n=0)^\infty \frac1{(2n+1)\binom{2n}n} = 1 + \frac12 \int_0^(1/2) (x^2 f''(x) + x f'(x)) \, dt

Integrate by parts.


\displaystyle \int_0^(1/2) x^2 f''(x) \, dx = \frac14 f'\left(\frac12\right) - 2 \int_0^(1/2) x f'(x) \, dx


\displaystyle \int_0^(1/2) x f'(x) \, dx = \frac12 f\left(\frac12\right) - \int_0^(1/2) f(x) \, dx

Then our sum is equivalent to


\displaystyle \sum_(n=0)^\infty \frac1{(2n+1)\binom{2n}n} = 1 + \frac18 f'\left(\frac12\right) - \frac14 f\left(\frac12\right) + \int_0^(1/2) \arcsin^2(x) \, dx

The remaining integral is fairly simple. Substitute and integrate by parts.


\displaystyle \int_0^(1/2) \arcsin^2(x) \, dx = \int_0^(\pi/6) u^2 \cos(u) \, du \\\\ ~~~~~~~~~~~~~~~~~~~~~~~~~ = (\pi^2)/(72) - 2 \int_0^(\pi/6) u \sin(u) \, du \\\\ ~~~~~~~~~~~~~~~~~~~~~~~~~ = (\pi^2)/(72) + \frac\pi{2\sqrt3} - 2 \int_0^(\pi/6) \cos(u) \, du \\\\ ~~~~~~~~~~~~~~~~~~~~~~~~~ = (\pi^2)/(72) + \frac\pi{2\sqrt3} - 1

Together with


f\left(\frac12\right) = 2 \arcsin^2\left(\frac12\right) = (\pi^2)/(18)


f'\left(\frac12\right) = \frac{4\arcsin\left(\frac12\right)}{\sqrt{1-\frac1{2^2}}} = (4\pi)/(3\sqrt3)

we conclude that


\displaystyle \sum_(n=0)^\infty ((n!)^2)/((2n+1)!) = \sum_(n=0)^\infty \frac1{(2n+1)\binom{2n}n} \\\\ ~~~~~~~~~~~~~~~~~~ = 1 + \left(\frac18\cdot(4\pi)/(3\sqrt3)\right) - \left(\frac14\cdot(\pi^2)/(18)\right) + \left((\pi^2)/(72) + \frac\pi{2\sqrt3} - 1\right) \\\\ ~~~~~~~~~~~~~~~~~~ = \boxed{(2\pi)/(3\sqrt3)}

User Audrey Dutcher
by
4.6k points